Biochemical analysis of Hel308 and HelQ helicases - Buckley, Ryan J. (2017)
DNA replication is an essential process conducted by the replisome. This large protein complex is continually challenged by DNA insults which hamper progression resulting in replication fork stalling or collapse. Paused replication forks contribute to a state of genome instability which is a major hazard for cells. Hel308 and HelQ are superfamily 2 helicases thought to promote genome stability in archaea and metazoans by acting at stalled replication forks. They participate in the early stages of recombination repair, responding to damage caused by DNA interstrand crosslinks. Both proteins are single stranded DNA stimulated ATPases which preferentially unwind forked DNA conferring a 3’ to 5’ polarity. DNA translocation is thought to occur through step wise movement of the helicase core, coupled to the actions of an accessory ratchet domain. These proteins possess an unconventional winged helix domain of unknown function. Protein/DNA interactions required for unwinding were investigated using chemically modified DNA substrates. Archaeal Hel308 showed sensitivity to an abasic site within the single stranded region and a methylphosphonate within the duplex region, suggesting essential base-stacking and electrostatic interactions. Human HelQ data contrasted this, eluding to a reliance on interactions within the duplex region. DNA binding affinities were also investigated using fluorescence anisotropy. Data suggested a role for Hel308 WHD in binding flayed duplex DNA and confirmed HelQ is able to bind a variety of DNA substrates. A third helicase; LHR, was successfully purified with the aim to collect single-molecule data as part of a collaboration.